USE OF DUSPATALIN (MEBEVERINE HYDROCHLORIDE) IN GASTROINTESTINAL DISEASES - Axmedov Shamshod Jamshidovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. Abdominal pain and spasms are common symptoms in organic gastrointestinal diseases, yet are associated with significant unmet need in terms of recognition and treatment. There was an examination of 20 patients who had cholecystectomy and have dysfunctional disorders of the Oddi's sphincter. All of the patients underwent the monotherapy with Mebeverine Retard in the dosage of 200 mg twice a day. The treatment efficiency was evaluated by the dynamics of clinical symptoms, results of the study of biochemical blood indices, data of the ultrasonic examination, and intragastric pH measurement. The aim of this review was to help physicians to understand the pathophysiology and impact to patients of abdominal pain and spasms in inflammatory bowel disease (IBD) and biliary diseases. This may in turn help in the selection of the most appropriate treatment to improve patients' overall daily functioning and quality of life in addition to reducing health resource utilization. Relative to the healthy colon, the mechanisms of pain generation in IBD include peripheral sensitization, including visceral hypersensitivity, central processing and modulation, and associated features or modifiers. Calcitonin gene related peptide, substance P, transient receptor potential vanilloid type, and serotonin biosynthesis in the colon are implicated in these processes.